Study of Rewetting Behavior in AHWR Fuel Cluster During Loss of Coolant with Water Jet Impingement - Debbarma, Ajoy (Nuclear science and engineering, 2025)
This study investigates the rewetting behavior of an Advanced Heavy Water Reactor (AHWR) fuel rod bundle during a loss-of-coolant accident using computational fluid dynamics simulations with ANSYS CFX. The analysis focuses on the cooling effectiveness of radial jet impingement at varying flow rates and its impact on rewetting temperature and wetting delay. Simulations were conducted by maintaining a constant initial wall temperature, with cooling curves and contour profiles extracted from various angular positions along the axial rod surfaces. The results reveal that rewetting is faster near the jet sections due to enhanced coolant interaction, while areas farther from the jets exhibit delayed wetting and elevated wall temperatures, where vapor accumulation hinders heat dissipation. Higher flow rates minimize wetting delays and improve cooling by promoting transition and nucleate boiling. However, irregular coolant splashing and vapor dominance disrupt the uniformity of rewetting across the bundle. The study highlights the limited impact of increased flow rates on achieving consistent rewetting along the entire rod length, with substantial fluctuations observed in cooling performance at different vertical positions. The findings emphasize the need for further research under high-temperature steam conditions to better understand boiling mechanisms and improve the stability of emergency cooling systems in nuclear reactors.